Analisis Faktor-Faktor Yang Mempengaruhi Keberlanjutan Usaha Umkm Bakso Ciwang Mang Ono Kabupaten Garut - Jihan Al Mahera; Helviani Rifdah Nazwa; Rinda Sekar Arum; Sofi Fadhilah Soliha; Nazwa Kameliah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The rapid growth of the culinary industry in Garut Regency, particularly within the Micro, Small, and Medium Enterprises (MSMEs) sector, has intensified competition and increased the need for businesses to maintain long-term sustainability. One notable phenomenon is the rising popularity of the MSME Bakso Ciwang Mang Ono, which went viral on social media despite the absence of a structured digital marketing strategy, yet remains able to sustain sales performance and consumer loyalty. This phenomenon indicates that business sustainability is not solely determined by economic factors but is also influenced by social, operational, and environmental dimensions. This study aims to analyze the factors affecting the business sustainability of Bakso Ciwang Mang Ono in Garut Regency. The research employs a mixed-method approach, combining quantitative analysis using Confirmatory Factor Analysis (CFA) with qualitative data obtained through observation and interviews. The research sample consists of 100 respondents selected through purposive sampling, specifically consumers who have made at least two purchases and are active users of social media. The CFA results reveal seven key factors influencing business sustainability: service and consumption experience, operational consistency, social factors, transparency and hygiene, product information, material efficiency, and community acceptance. Among these, service and consumption experience emerged as the most dominant factor. These findings reinforce the Triple Bottom Line concept, which emphasizes the integration of economic, social, and environmental aspects in the sustainability of culinary MSMEs. This study provides practical implications for MSME practitioners to prioritize service quality, operational consistency, and resource efficiency to ensure business sustainability in the digital era.